Implementation of Good Governance in the Institutional Structure of the General Elections Commission (KPU) as an Election Organizer in Gunungkidul Regency, Yogyakarta Province - R.A. Dyah Ayu Mega Pangarsi; Tijan Tijan (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2025)
This study examines how the principles of good governance are implemented in the Gunungkidul Regency KPU as the election organizer in Gunungkidul Regency, as well as looking at the resources involved in the application of good governance principles. The purpose of this study is to see how the implementation is carried out and the resources involved in the KPU. The methods used in this research are qualitative and descriptive, employing interviews and documentation. This research provides an overview of how the KPU institution implements good governance principles to improve public services and services during elections. In the implementation of good governance at the Gunungkidul Regency KPU, these principles have been well applied, and the human and technological resources are also adequate. Coordination between the KPU, other institutions, and the community is well-coordinated. Hopefully, this research can serve as a reference for the KPU of Gunungkidul Regency itself and other institutions aiming to continuously improve public services for the general public.